Human capital theory and venture capital firms: exploring “home runs” and “strike outs” - Dimov, Dimo P.; Shepherd, Dean A. (Journal of Business Venturing, 2005)
Using a human capital perspective, we investigated the relationship between the education and experience of the top management teams of venture capital firms (VCFs) and the firms' performance. We found that although general human capital had a positive association with the proportion of portfolio companies that went public [initial public offering (IPO)], specific human capital did not. However, we did find that specific human capital was negatively associated with the proportion of portfolio companies that went bankrupt. Interestingly, some findings were contrary to expectations from a human capital perspective, specifically the relationship between general human capital and the proportion of portfolio companies that went bankrupt. Future research is suggested.